Can power Doppler ultrasound of the entheses help in classifying recent axial spondyloarthritis? Data from the DESIR cohort. Issue 2 (22nd August 2018) - Poulain, Cecile; D'Agostino, Maria Antonietta; Thibault, Severine; Daures, Jean Pierre; Ferkal, Salah; Le Corvoisier, Philippe; Rahmouni, Alain; Loeuille, Damien; Dougados, Maxime; Claudepierre, Pascal
Abstract : Early diagnosis of axial spondyloarthritis (axSpA) remains a challenge due to the lack of specificity of clinical symptoms and variable prevalence of axial imaging findings permitting a definite diagnosis. Power Doppler ultrasonography (PDUS) of the entheses has demonstrated to be a potential useful tool for the classification and diagnostic management of early SpA independently of the phenotype. Objectives: To assess the classification value (sensitivity and specificity) of PDUS-defined enthesitis for identifying patients fulfilling Assessment of SpondyloArthritis international Society (ASAS) classification criteria for axSpA (ASAS+) in patients with recent inflammatory back pain (IBP) (the DESIR (DEvenir des Spondylarthropathies Indifférenciées Récentes) cohort). Methods: Baseline PDUS was performed at eight entheseal sites, and PDUS enthesitis was defined by the presence of vascularisation at entheseal insertion. Results: 402 patients from the DESIR cohort underwent a PDUS evaluation. PDUS enthesitis was detected in 58 (14.4%) patients of whom 40 (14.2%) belonged to the ASAS+ patients and 18 (17%) to the ASAS- patients. The sensitivity of PDUS enthesitis was 13.9% and the specificity was 83.5%, with a positive predictive value of 69% and 26.8% of negative predictive value for meeting ASAS criteria for axSpA. Of the 18 ASAS- patients with positive PDUS, 59% fulfilled Amor's criteria, 88% European Spondyloarthropathy Study Group criteria and 59% both. Conclusions: In a cohort of patients with recent IBP, the prevalence of PDUS enthesitis was low (14.4%); however, its specificity for classifying patients as axSpA according to ASAS criteria was high (83.5%). PDUS enthesitis might be of additional value for classifying as patients with axSpA IBP who do not fulfil ASAS criteria.